Biomechanics of a pedestrian accident reconstruction - Portal, Ricardo (2019)
Pedestrians represent about 20% of the overall fatalities in Europe's road traffic accidents, as well as in Portugal. An in-depth investigation, accident reconstruction, is mandatory in order to analyze with care fundamental aspects of an accident. Detailed information about the injuries and injury causation mechanisms are with great use for it. Accident reconstruction computational techniques using pedestrian biomechanical models are used to evaluate the accident conditions that lead to major pedestrian injuries, such as the vehicle's speed and the impact location. For biomechanical injury criterions, the AIS (Abbreviated Injury Scale), the HIC (Head Injury Criterion) and some other injury criterions are used. Pedestrian's height, weight, gender, age, vehicle geometry (or category) and travelling speed, significantly influence the pedestrian injuries in the event of a road collision. The use of injury scales and biomechanical criterions in the in-depth accident investigation of road accidents, such as AIS, can improve significantly the quality of the reconstruction process. The computer simulation of vehicle-to-pedestrian collisions is fundamental for the study of the dynamics of these road accidents. Where did the pedestrian is when the vehicle hits him? Normally, there is no simple and clear answer. The pedestrian, if survives, states that he uses the crossway, the driver of the vehicle states otherwise, that the location of the pedestrian was much later than the pedestrian crossing. This work presents an accident where only the use of accident reconstruction specialized software, PC-Crash, conjugated with all available information allowed the determination of the vehicle's speed and the Location of the pedestrian.